2011
DOI: 10.1055/s-0031-1300151
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Factors Affecting the Complex Formation between Deferiprone (L1) and Cu(II)

Abstract: Deferiprone (1,2-dimethyl-3-hydroxypyrid-4-one, L1, CAS 30652-11-0) is a new chelating drug used worldwide for the treatment of iron overloading conditions. Spectrophotometric and potentiometric measurements were carried out to investigate the interaction of L1 with Cu(II) ions under different conditions. The complexation of Cu(II) ions with L1 in aqueous solution leads predominantly to the formation of the Cu(L1)2 species at a pH range of 4-9. The experimental results indicate that L1 has high affinity for Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…For instance, deferiprone has been widely used for the treatment of systemic iron-related diseases and for neurological pathologies, including PD [72], due to its low molecular weight and ability to cross the blood-brain barrier. Different studies demonstrated deferiprone's ability to chelate not only iron but also copper, aluminum and zinc [73], reducing their free radical catalytic activity [74]. Moreover, multifunctional iron/copper chelating agents have been evaluated even if their clinical translation has not yet progressed [75].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…For instance, deferiprone has been widely used for the treatment of systemic iron-related diseases and for neurological pathologies, including PD [72], due to its low molecular weight and ability to cross the blood-brain barrier. Different studies demonstrated deferiprone's ability to chelate not only iron but also copper, aluminum and zinc [73], reducing their free radical catalytic activity [74]. Moreover, multifunctional iron/copper chelating agents have been evaluated even if their clinical translation has not yet progressed [75].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…It is more soluble in acid, for example in the stomach than in alkaline or neutral pH conditions. It is sparingly soluble in water at pH 7.4 (about 20 mg/ml, at 37 C) and forms red colour complexes with iron, green complexes with copper, blue complexes with uranium and colourless complexes with aluminium (38)(39)(40)(41). The affinity of L1 for iron is greater than copper, aluminium, zinc, indium, gallium and uranium and other metals at pH 7.4 (24).…”
Section: Chemical and Pharmacological Properties Of Deferipronementioning
confidence: 99%
“…The design of these compounds was based on deferiprone (1,2-dimethyl-3-hydroxypyridin-4-one), which is a globally used iron-chelating drug. In vitro studies have shown that Cu II and Zn II are the most competitive metal ions against Fe III and are able to considerably affect the formation of Fe III complexes of these iron chelators (Clarke & Martell, 1992;Pashadilis & Kontoghiorghes, 2001;Li, 2019). Investigating the complexation of HPCs to Cu II and Zn II is of importance as the displacement of these essential metal ions by chelating drugs could adversely affect the biological processes dependent on these metals, potentially causing toxicity.…”
Section: Introductionmentioning
confidence: 99%